A propósito de las primeras arquitecturas castreñas en el sector occidental de Asturias - Ríos González, Sergio (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2019)
This paper deals with the analysis of the architectural evidence linked to the earliest defined occupation phases in western asturian hillforts. We realise that there is no known parallelisms to the period’s most representative archaeological structures, and are equally aware of the difficulty to assign the whole recovered evidence to the 9th-8th centuries BC. Therefore, and waiting for future new data which would help to solve the question, we propose to locate the emergence of the hillforts settlement in this area within a more expanded and later time, between the 8th and the 5th centuries BC.